TINJAUAN LARANGAN KEPEMILIKAN HAK PRIBADI ATAS LUAS TANAH PERTANIAN YANG MELEWATI BATAS KEPEMILIKAN DI KECAMATAN TEBING TINGGI TIMUR KABUPATEN KEPULAUAN MERANTI (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Indonesia is an agricultural country, land is an absolute thing that must be owned by an agrarian society. The importance of land for human life is because every human being needs land because there are no activities or activities of people who do not need land. Land contains various kinds of natural resources that can be utilized by humans. Land is one of the main sources for the survival and livelihood of the nation. Therefore, land is a basic need for every human being. With the rapid population growth, it can cause land to be scarce and limited in achieving the prosperity of the people, which is divided fairly and evenly, for the welfare of the people, the land has the potential to be cultivated or used to fulfill real needs by improving agriculture. In this regard, the provision, designation, control, use and maintenance of them need to be regulated in order to guarantee legal certainty in their control and utilization and at the same time legal protection for the people at large, especially the farmers, while maintaining the sustainability of their ability to support sustainable development activities.The research conducted was sociological juridical legal research. Research conducted directly to respondents as the main data. This research requires primary data as the main data supported by secondary data consisting of primary and secondary legal materials and tertiary legal materials. The results showed that the factors causing large-scale land ownership are the lack of legal awareness of the community, law enforcement factors, facilities and infrastructure factors and economic factors. For this reason, the Land Office has made efforts to overcome the occurrence of large-scale land ownership in Tebing Tinggi Timur Subdistrict, Meranti Islands Regency, by carrying out law enforcement. Furthermore, to prevent large-scale land ownership, it is necessary to coordinate between the Land Office and related agencies, namely the Camat, the Village Head and the Bapoktan. In addition, the current provisions prohibiting largescale land ownership still need to be reviewed to adapt to current developments and community needs. Keywords: Privately Owned Land Beyond The Boundary